The Use of Facebook Fanpage as Promotional Media for the Novel Book Fans by Using the Model of SMCR Berlo - Sutanto, Shienny Megawati (Universitas Ciputra, 2016)
The purpose of this research is to find out how Facebook fanpage can be used as media to promote novel for novel book fans by using SMCR Berlo models. This research use qualitative method s with interpretatif paradigm and fenomenologi aproach. The focus of this research is how to use publisher’s Facebook fanpage social network as a promotional media. The results from this research shows that promotion from the publisher through Facebook fanpage can be utilized to the maximum by interactive or two-way communication that occurs between a publisher with novel readers.